Studi Penggunaan Media Virtual Pada Pendidikan Kejuruan di Indonesia - Marko Ayaki Lumbantobing; Ahmad Eko Suryanto; Ratna Pancawati (Journal on Education, 2024)
The use of virtual media in learning is one of the innovations in the use of technology in learning. This research uses content analysis of articles in vocational education journals that discuss the use of virtual media in learning. The results of this study show that the number of publications on the use of virtual media in vocational education was highest in 2019 during the pandemic. The most used research type is R&D where the field of mechanical engineering is the target of the most frequent use of virtual media. The platform most often used in the use of virtual media is PC/Laptop. The overall research shows that the use of virtual media in vocational education in Indonesia shows a positive impact. This study also provides recommendations in the form of integrating virtual media into the vocational education curriculum for a better learning experience.